Akad Musyarakah Mutanaqisa: Inovasi Baru Produk Pembiayaan Bank Syariah - Putri Dona Balgis (JESI (Jurnal Ekonomi Syariah Indonesia), 2017)
Product based partnersip with profit-loss sharing like Musyarakah as acompetitive product in Islamic Banking has not showed significant growthlike another products. One of derivative contract of musyarakah which ispotentially practiced as an innovation product in Islamic banking ismusyarakah mutanaqisa contract. This study decribes  about musyarakahmutanaqisa contract, the difference between musyarakah mutanaqisa andconventional lease, the treatment of accounting, and the practice ofmusyarakah mutanaqisa in Indonesia. In Indonesia, four of thirteen IslamicBanks in Indonesia offer a financing product with musyarakah mutanaqisacontract. They are Bank Muamalat, Maybank Syariah, Panin Bank Syariah,and Bank Mega Syariah.